2020
DOI: 10.1186/s12876-020-01348-2
|View full text |Cite
|
Sign up to set email alerts
|

The NETest liquid biopsy is diagnostic for gastric neuroendocrine tumors: observations on the blood-based identification of microscopic and macroscopic residual disease

Abstract: Background NETest, a novel multi-gene liquid biopsy has utility in neuroendocrine tumor (NET) diagnosis and identification of residual disease. We independently assessed utility of the NETest to diagnose gastric neuroendocrine neoplasms (GNENs) and identify micro- and macroscopic residual disease. Methods Cohorts comprised histologically confirmed GNENs at biopsy, n = 46; GNETs Type 1: 42 (32 NET G1, 10 NET G2), a GNET Type 3: 1 well-different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
1
6
0
2
Order By: Relevance
“…Studies on the clinical use of NETest in the Polish population have confirmed the earlier reports regarding its usefulness in the diagnosis of NENs of the gastrointestinal tract [33,43], respiratory system [44][45][46], pheochromocytoma and paraganglioma [29,30,47], as well as correlations with imaging tests [43] and disease activity (progression) [13,43,46,48]. A comparison of the clinical utility of NETest and circulating chromogranin A demonstrated a significant advantage of the molecular biomarker in the diagnosis and monitoring of NENs [48][49][50][51].…”
Section: Guidelinessupporting
confidence: 61%
See 1 more Smart Citation
“…Studies on the clinical use of NETest in the Polish population have confirmed the earlier reports regarding its usefulness in the diagnosis of NENs of the gastrointestinal tract [33,43], respiratory system [44][45][46], pheochromocytoma and paraganglioma [29,30,47], as well as correlations with imaging tests [43] and disease activity (progression) [13,43,46,48]. A comparison of the clinical utility of NETest and circulating chromogranin A demonstrated a significant advantage of the molecular biomarker in the diagnosis and monitoring of NENs [48][49][50][51].…”
Section: Guidelinessupporting
confidence: 61%
“…A negative test result (< 20%) excludes NEN or indicates a history of radical removal of the tumour; a positive test result (≥ 20%) correlates with the diagnosis of neuroendocrine neoplasm without identifying the primary tumour site [29,30]. Clinical use of NETest also includes the identification of microscopic disease [33,34], assessment of the radicality of surgical treatment [15,35], somatostatin analogues [13], radioisotope [36], and disease progression [37]. A test score between 20 and 40% indicates disease stabilisation, while a score between 41 and 100% indicates disease progression [38,39].…”
Section: Incidence and Epidemiologymentioning
confidence: 99%
“…Despite all patients were disease free at endoscopical, radiological, and functional imaging, the NETest score was elevated in 6 patients, suggesting that these patients could have minimal residual disease. According to this hypothesis, the same study demonstrated that in case of microscopical residual disease evidenced at histological examinations (5 patients with positive polypectomy margin and 4 patients with random biopsies diagnostic for microscopic tumor), NETest was elevated (28 ± 9%), demonstrating the accuracy of this diagnostic instrument in detecting minimal residual disease before morpho-functional imaging [51].…”
Section: Resultsmentioning
confidence: 99%
“…NETest can detect disease progression 5–24 months before imaging changes. Identification of MRD that cannot be detected by imaging studies should lead to earlier therapeutic intervention in GEP-NENs [ 76 , 78 ]. Follow-up of GEP-NENs requires frequent endoscopy with biopsy and/or CT scanning, which causes physical pain and radiation exposure, and is costly.…”
Section: Biomarkersmentioning
confidence: 99%